FAKTOR-FAKTOR YANG MEMENGARUHI PEMENUHAN HAK-HAK REPRODUKSI DALAM BER-KELUARGA BERENCANA PADA WANITA PASANGAN USIA SUBUR YANG BEKERJA DI RUMAH SAKIT UMUM MATERNA MEDAN TAHUN 2013 - julia alistawaty purba; Erna Mutiara; Heru Santosa (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT The fullfillment of reproductive rights in family planning among women of reproductive age couples includes the fullfillment of the rights in the number of children, birth interval, and the selection of contraceptive. Indonesian population census in 2010 and the Indonesian Demography Health Survey (IDHS) preliminary report in 2012 indicated the existence of gaps in this fullfillment. This study aimed to analyze the factors influenced the fullfillment of reproductive rights in family planning among women of reproductive age couples who worked at Materna general hospitals in 2013. The design of the study was cross sectional study. The population of this study were the women of reproductive age couples and samples consisted of 61 people. The results showed that only 28(45.9%) respondents were fullfilled their reproductive rights in family planning. There were relationship between knowledge (p = 0.030), attitude (p = 0.0001), income level (p = 0.023), husband's support (p = 0.013), social support (p = 0.001) with the fullfillment of reproductive rights in family planning except status of women in the family (p = 0.274). Simultaneously variables that significantly influenced on the fullfillment of women's reproductive rights in family planning were the attitude (p = 0.017) and social support (p = 0.029). It is expected that the women of reproductive age couples worked at the Materna general hospital should be more increase the concern and the responsibility along with her husband and family in order to implement the reproductive function.Key word : Reproductive Rights in Family Planning, Women of Reproductive Age Couples, Materna